Spectroscopic and microscopic investigations of tautomerization in porphycenes: condensed phases, supersonic jets, and single molecule studies. Issue 7 (7th February 2017) - Fita, P.; Grill, L.; Listkowski, A.; Piwoński, H.; Gawinkowski, S.; Pszona, M.; Sepioł, J.; Mengesha, E.; Kumagai, T.; Waluk, J.
Abstract : Tautomerization of porphycene, coherent in supersonic jets and a rate process in solutions, can be controlled for single molecules on surfaces. Abstract : We describe various experimental approaches that have been used to obtain a detailed understanding of double hydrogen transfer in porphycene, a model system for intramolecular hydrogen bonding and tautomerism. The emerging picture is that of a multidimensional tautomerization coordinate, with several vibrational modes acting as reaction-promoters or inhibitors through anharmonic intermode coupling. Tunnelling processes, coherent in the case of isolated molecules and incoherent in condensed phases, are found to play a major role even at elevated temperatures. Single-molecule spectroscopy studies reveal large fluctuations in hydrogen transfer rates observed over time for the same chromophore. Scanning probe microscopy is employed to directly observe the structure and tautomerization dynamics of single molecules adsorbed on metal surfaces and demonstrates how the interactions of the molecules with atoms of the supporting surface affect their static and dynamic properties: different tautomeric forms are stabilized for molecules depending on the surface structure and the reaction mechanism can also change, from a concerted to a stepwise transfer. The scanning probe microscopy studies prove that tautomerization in single molecules can be induced by different stimuli: heat, electron attachment, light, and force exerted by the microscope's tip. Possible applications utilizing tautomerism are discussed in combination with molecular architectures on surfaces, which could pave the way for the development of single-molecule electronics.